A penalty method and a regularization strategy to solve MPCC - Monteiro, M. Teresa T. (2011)
The goal of this paper is to solve mathematical programme with complementarity constraints using nonlinear programming techniques. This work presents two algorithms based on several nonlinear techniques such as sequential quadratic programming, penalty techniques and regularization schemes. A set of AMPL (A Modeling Language for Mathematical Programming) problems were tested and the computational experience shows that both algorithms are effective.